A gradient ceramic intumescent fire retardant coating and its preparation method and application

By using gradient ceramicized expansion fire-retardant coating, the coating expands at high temperature and undergoes ceramicization reactions to form a hard ceramic layer and a porous carbonization layer, solving the problem that existing fire-retardant coatings are prone to damage in high impact fires, and achieving effective fire protection and thermal protection for the battery pack.

CN119463563BActive Publication Date: 2025-04-29ANHUI ESTONE MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510038559.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-29
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing fire-resistant coatings are prone to damage in high impact fires, resulting in poor overall safety of the battery pack.

Method used

Gradient ceramic expanded fire-retardant coating is used, which consists of film-forming substances, flame retardants, multi-melting temperature ceramic powders and reinforced fibers. The coating expands when heated and undergoes gradient ceramicization from the outside to the inside, forming a hard ceramic layer and a porous carbonized layer to enhance fire resistance.

Benefits of technology

During open flame ablation, the coating can remain intact, block heat transfer, provide long-term stable fire protection, and enhance the safety of the battery pack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463563B_ABST
    Figure CN119463563B_ABST
Patent Text Reader

Abstract

The present invention discloses a gradient ceramic expansion type fire retardant coating and a preparation method and application thereof, and relates to the technical field of fire retardant coatings. The gradient ceramic expansion type fire retardant coating comprises a film-forming substance, a flame retardant 10-50%, a ceramic powder 20-50%, a reinforcing fiber 0-10%, and an additive 0-10%; the ceramic powder is composed of at least three glass powders with different melting temperatures, wherein the weight ratio of the first glass powder, the second glass powder and the third glass powder is (1-6): (1-6): (1-6), so that the coating can form a gradient ceramic expansion layer in a fire. Compared with the prior art, the ceramic expansion layer of the present invention does not cause droplets, breakage and the like at high temperatures, and can provide long-term stable and reliable thermal protection for metal substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fire retardant coatings, and in particular to a gradient ceramic intumescent fire retardant coating and a preparation method and application thereof. Background Art

[0002] Since Sony launched the world's first commercial lithium-ion battery in 1991, lithium-ion batteries have attracted attention from battery researchers in various countries for their high energy density, no memory effect and high cycle life. After more than 30 years of development, lithium-ion batteries have become the main battery in the field of power batteries. However, during use, lithium-ion batteries are subjected to external forces such as collision, extrusion and impact, which cause thermal weight loss, leading to spontaneous combustion and even explosion of the battery pack.

[0003] At present, the passive fire protection of power battery packs mainly includes flame retardant foam, aerogel, ceramic silicone rubber and fire retardant coatings. Among them, fire retardant coatings have attracted widespread attention due to their advantages such as low cost and convenient construction methods.

[0004] CN114015261A discloses an inorganic water-resistant zero-VOC ceramic intumescent fire-retardant coating and its preparation method and application, but its filler is mainly metal oxide, and its breakdown voltage and volume resistivity are both low. If it is used for fire protection of battery packs, it may cause short circuit and lead to battery damage.

[0005] CN107033734 A discloses a ceramicizable epoxy resin fire retardant coating, but its ceramicization condition is high-temperature sintering in a muffle furnace, and the open flame ablation experiment is conducted using a low-temperature, low-impact alcohol torch at 700-1000°C, which cannot adapt to actual battery pack fires and cannot achieve rapid ceramicization.

[0006] Therefore, it is of practical significance to develop a fire-retardant coating that can expand rapidly and undergo a ceramic reaction when burned by an open flame. Summary of the invention

[0007] In order to solve the problem that the expansion layer of the fire retardant coating in the prior art has poor mechanical properties and is easily damaged in high-impact fires, resulting in poor overall safety of the battery pack, the present invention will provide a gradient ceramic expansion type fire retardant coating and a preparation method thereof.

[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0009] The first object of the present invention is to provide a gradient ceramic intumescent fire retardant coating, comprising the following components in weight percentage:

[0010] Film-forming substances 20~50%

[0011] Flame retardant 10~50%

[0012] Ceramic powder 20~50%

[0013] Reinforced fiber 0~10%

[0014] Additives 0~10%;

[0015] The ceramic powder comprises a first glass powder, a second glass powder and a third glass powder;

[0016] The initial melting point of the first glass powder is 400-600° C.;

[0017] The initial melting point of the second glass powder is 601-900°C;

[0018] The initial melting point of the third glass powder is 901-1100°C.

[0019] The second object of the present invention is to provide the application of the gradient ceramic intumescent fire retardant coating in a power battery pack.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention adopts a composite system of film-forming materials, flame retardants and multi-melting temperature ceramic powders. The coating will expand when heated. As the high temperature continues, the expansion layer will undergo gradient ceramicization from the outside to the inside, gradually forming a gradient structure of "ceramic layer-hard carbon layer-carbonized layer". The hard ceramic layer on the surface can resist the ablation of high-impact flames and keep the expansion layer intact. The internal porous structure can effectively block the transfer of heat, providing long-term and stable fire protection for the metal substrate.

[0022] 2. The present invention adopts ceramic powders with multiple melting temperatures and adds zinc borate, silicon carbide fiber, etc. as ceramic promoters, so that the coating has the performance of low-temperature rapid ceramicization; the coating undergoes a gradient melting-crystallization reaction during open flame ablation, and the expansion layer undergoes a gradient ceramic reaction from the outside to the inside, overcoming the defects of existing ceramic coatings such as droplets and detachment from the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the structure of the gradient ceramic intumescent fire retardant coating of the present invention after being heated;

[0024] Among them, 1-ceramic layer; 2-hard carbon layer; 3-carbonized layer;

[0025] Figure 2 This is a cross-sectional view of the expansion layer of the coating obtained in Example 1 after ablation for 30 minutes;

[0026] Figure 3 This is the state of the expansion layer of the coating obtained in Comparative Example 1 after ablation for 30 minutes;

[0027] Figure 4 This is the state of the expansion layer of the coating obtained in Comparative Example 6 after ablation for 30 minutes;

[0028] Figure 5 The back temperature curve of the substrate during the 30-min ablation of the coating obtained in Example 1;

[0029] Figure 6 This is a test diagram of the expansion layer strength after the coating was ablated for 30 minutes obtained in Example 1;

[0030] Figure 7 This is a test chart of the expansion layer strength of the coating obtained in Example 16 after 30 minutes of ablation. DETAILED DESCRIPTION

[0031] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0032] The present invention provides a gradient ceramic intumescent fire retardant coating, comprising the following components in weight percentage:

[0033] Film-forming substances 20~50%

[0034] Flame retardant 10~50%

[0035] Ceramic powder 20~50%

[0036] Reinforced fiber 0~10%

[0037] Additives 0~10%;

[0038] The ceramic powder comprises a first glass powder, a second glass powder and a third glass powder;

[0039] The initial melting point of the first glass powder is 400-600° C.;

[0040] The initial melting point of the second glass powder is 601-900°C;

[0041] The initial melting point of the third glass powder is 901-1100°C.

[0042] In the present invention, the weight ratio of the first glass powder, the second glass powder and the third glass powder is (1-6): (1-6): (1-6). Under preferred conditions, the weight ratio of the first glass powder, the second glass powder and the third glass powder is (1-3): (1-3): (1-3).

[0043] Under preferred conditions, the total weight percentage of the first glass powder, the second glass powder and the third glass powder in the gradient ceramic intumescent fire retardant coating is 15-45%.

[0044] In the present invention, the film-forming material includes but is not limited to at least one of epoxy resin, acrylic resin, epoxy silicone resin, phenolic resin, polyurethane resin, polyester resin, alkyd resin, and polystyrene resin. When the film-forming resin is epoxy resin, the film-forming material further includes a curing agent.

[0045] Under preferred conditions, the weight percentage of the epoxy silicone resin in the film-forming substance is not less than 10%, based on the total weight of the film-forming substance; further preferably, the weight percentage of the epoxy silicone resin in the film-forming substance is 10-70%, more preferably 30-50%.

[0046] In the present invention, the flame retardant includes but is not limited to at least one of ammonium polyphosphate, melamine, aluminum hydroxide, magnesium hydroxide, pentaerythritol and dipentaerythritol.

[0047] Under preferred conditions, the gradient ceramic intumescent fire retardant coating comprises 10-20% ammonium polyphosphate and 5-10% melamine, based on the total weight of the gradient ceramic intumescent fire retardant coating.

[0048] Under preferred conditions, the ceramic powder further comprises at least one of silicon carbide, aluminum phosphate, calcium carbonate, titanium dioxide, and zinc borate.

[0049] In the present invention, the reinforcing fiber may be any reinforcing fiber known to those skilled in the art, including but not limited to at least one of silicon carbide fiber, alumina fiber, glass fiber, silicon oxide fiber, and carbon fiber.

[0050] Under preferred conditions, the reinforcing fiber has a diameter of 2-10 μm and a length of 0.05-3 mm.

[0051] In the present invention, the auxiliary agent may be an auxiliary agent well known to those skilled in the art, including but not limited to at least one of a rheological agent, a dispersant, a thickener, an anti-settling agent, a leveling agent, a defoaming agent, and an anti-sagging agent.

[0052] In the present invention, the preparation method of the gradient ceramic intumescent fire retardant coating may be a coating preparation method well known to those skilled in the art. Exemplarily, the preparation method of the gradient ceramic intumescent fire retardant coating comprises the following steps:

[0053] (1) uniformly mixing a flame retardant and a ceramic powder according to a ratio to obtain a powder mixture;

[0054] (2) fully mixing the film-forming substance and the additive according to the ratio, and then adding the above powder mixture, mixing evenly to obtain a slurry;

[0055] (3) Add reinforcing fibers to the slurry according to a proportion and mix them evenly to obtain a gradient ceramic intumescent fire retardant coating.

[0056] In some preferred embodiments of the present invention, the flame retardant and the ceramic powder are sieved separately. The sieving can remove a small amount of substances with larger particle sizes that may exist in the powder raw materials, making the coating system more uniform.

[0057] The present invention also provides an application of the gradient ceramic intumescent fire retardant coating in a power battery pack. Specifically, the gradient ceramic intumescent fire retardant coating is evenly mixed with a curing agent and then coated on the surface of a metal substrate and cured to obtain a gradient ceramic intumescent fire retardant coating.

[0058] The present invention will be described in detail below through specific embodiments.

[0059] The test method for the flame retardant and heat-insulating properties of the fire retardant coating in the present invention is as follows: the fire retardant coating and the curing agent are evenly mixed and then sprayed on the surface of the Q235 steel plate, the spraying thickness is 500 μm, and the coating is cured at room temperature for 48 hours. Then, a flame is used to vertically ablate the Q235 steel plate covered by the coating, and the temperature of the side of the steel plate away from the flame is measured. The ablation flame temperature is 1200°C and the ablation time is 30 minutes.

[0060] The dielectric strength is obtained by the standard IEC60243 test; the volume resistivity is obtained by the standard IEC60093 test.

[0061] All raw materials in the following examples are commercially available.

[0062] Epoxy resin was purchased from Huntsman, model number GT-7072;

[0063] The polyetheramine curing agent was purchased from Huntsman, model number D2000;

[0064] Epoxy silicone resin was purchased from Yangzhou Lida Resin Co., Ltd., model LD-3196;

[0065] Ammonium polyphosphate was purchased from Zhenjiang Xingxing Flame Retardant Co., Ltd., model APP-0M;

[0066] Melamine was purchased from Jiangsu Oumao Chemical Co., Ltd., model OM-032;

[0067] Aluminum hydroxide was obtained from Anhui Yishitong Materials Technology Co., Ltd., model ATH-0010;

[0068] Low melting point glass powder was purchased from Guangdong Qichen New Material Technology Co., Ltd., including low melting point glass powder D245 with an initial melting point of 450°C (hereinafter referred to as glass powder A), low melting point glass powder D275 with an initial melting point of 750°C (hereinafter referred to as glass powder B), low melting point glass powder D295 with an initial melting point of 950°C (hereinafter referred to as glass powder C), and low melting point glass powder D260 with an initial melting point of 600°C (hereinafter referred to as glass powder D);

[0069] Zinc borate was sourced from Anhui Yishitong Materials Technology Co., Ltd., model number ZB03-500;

[0070] Glass fiber was purchased from Dongguan Rongtai Chemical Co., Ltd., model EMG-400;

[0071] Fumed silica was purchased from Evonik Industries, model R972;

[0072] The phosphate ester was sourced from Anhui Yishitong Materials Technology Co., Ltd., model number FPE4H.

[0073] Example 1

[0074] The raw material composition and proportion of the gradient ceramic intumescent fire retardant coating prepared in this embodiment are shown in Table 1.

[0075] Table 1

[0076]

[0077] The preparation of ceramic intumescent fire retardant coating is carried out according to the raw material composition and ratio in Table 1, including the following steps:

[0078] (1) fully mixing the flame retardant and ceramic powders, sieving them, and obtaining a powder mixture;

[0079] (2) fully mixing the film-forming substance and the additive, and then adding the above powder mixture, mixing evenly to obtain a slurry;

[0080] (3) Add reinforcing fibers to the slurry and mix them evenly to obtain a gradient ceramic intumescent fire retardant coating.

[0081] The flame retardant and heat-insulating properties of the gradient ceramic intumescent fire retardant coating obtained in Example 1 were tested. The coating was not damaged during the ablation process, and the height of the expansion layer was 10.6 mm after 30 minutes of ablation. The expansion multiple reached 21.2 times, and the back temperature was finally stabilized at around 260°C.

[0082] Figure 1 This is a schematic diagram of the structure of the gradient ceramic intumescent fire retardant coating after being heated. Figure 2 This is a cross-sectional view of the expansion layer of the coating obtained in Example 1 after ablation for 30 minutes. Figure 1 and Figure 2 It can be seen that the expansion layer has a dense porous structure inside and an obvious gradient structure from the outside to the inside, namely, it includes: an outer layer of white flaky ceramic layer 1, a middle layer of dense hard carbon layer 2 and an inner layer of loose porous carbonized layer 3.

[0083] Figure 5 The back temperature curve of the substrate during the 30-min ablation of the coating obtained in Example 1 is shown in FIG. Figure 5 It can be seen that when the substrate coated with the coating is ablated by an open flame at 1200°C, the back temperature of the substrate rises rapidly to 230°C within the first 10 minutes; within the 10th to 20th minutes, the back temperature of the substrate slowly rises to 260°C; within the 20th to 30th minutes, the back temperature of the substrate stabilizes at 260°C, which indicates that the coating prepared in Example 1 has excellent thermal protection effect.

[0084] Figure 6 This is a graph showing the strength of the expansion layer after 30 minutes of ablation of the coating obtained in Example 1. Figure 6 It can be seen that 4 500g weights are placed directly above the expansion layer, with a total weight of 2kg, and there is no obvious collapse on the surface of the expansion layer, which indicates that the expansion layer after ablation in Example 1 can support at least 2kg of weight without damage.

[0085] The dielectric strength and volume resistivity of Example 1 of the present invention have been tested, and the dielectric strength is >13kV / mm, and the volume resistivity is >1.4×10 15 Ω·cm, therefore, the insulation of the coating prepared by the present invention meets the requirements of fire retardant coating for batteries.

[0086] Examples 2 to 7 and Comparative Examples 1 to 2

[0087] The method of Example 1 is followed, except that the weight ratio of glass powder A, glass powder B, and glass powder C is kept unchanged (1:2:1), and the total amount of the three glass powders is adjusted, as shown in Table 2.

[0088] Table 2

[0089]

[0090] From Table 2 we can see that:

[0091] When the total amount of glass powder is 20%, the distribution ratio of each group is the most coordinated, which not only ensures sufficient expansion multiples after ablation, but also forms a sufficiently hard gradient ceramic structure, so the back temperature of the substrate is the lowest, only 260°C.

[0092] When the total amount of glass powder increases, the content of film-forming substances and flame retardants in the coating will be relatively reduced, so that the height and expansion multiple of the expansion layer of the coating will decrease after 30 minutes of ablation, which will lead to an increase in the back temperature of the substrate. In particular, when the total amount of glass powder reaches 50%, its expansion multiple is only 8.2 times, which cannot provide effective heat insulation, and the back temperature of the substrate is as high as 340℃.

[0093] When the total amount of glass powder is reduced, the content of ceramic powder in the coating decreases relatively, and it is impossible to form a hard and dense gradient ceramic expansion layer during continuous ablation. Although its expansion height and expansion thickness increase, its density decreases, resulting in poor thermal insulation effect. Especially when the total amount of glass powder is only 10%, the height of its loose expansion layer reaches 16.9mm, and the expansion multiple is 33.8 times, but the thermal insulation effect is poor, and the back temperature of the substrate is as high as 330℃.

[0094] Figure 3 This is the state of the expansion layer of the coating obtained in Comparative Example 1 after 30 minutes of ablation. Figure 3 It can be seen that the expansion layer is obviously damaged where it is directly burned by the flame, and there is a ceramic structure around the damaged part. This shows that although the coating prepared in Comparative Example 1 can also undergo expansion and ceramic reaction during the ablation process, its ceramic strength is low and it is easy to be damaged, and it cannot effectively play a role in fire prevention and heat insulation.

[0095] Examples 8 to 13 and Comparative Examples 3 to 8

[0096] The method of Example 1 is followed, except that the total amount of the three glass powders is kept unchanged (20%), and the amount ratio of glass powder A, glass powder B, and glass powder C is adjusted, as shown in Table 3.

[0097] Table 3

[0098]

[0099] From Table 3 we can see that:

[0100] As shown in Comparative Examples 3 to 5, when only one type of low-melting-point glass powder is added, the ceramic strength of the expansion layer after 30 minutes of ablation is low and will be damaged during the ablation process; as shown in Comparative Examples 6 to 8, when two types of low-melting-point glass powder are added, the expansion layer after ablation will remain intact and will not be damaged, but the back temperature of the substrate will reach above 300°C, and the thermal protection performance is poor; when three types of low-melting-point glass powder are added, the expansion layer after ablation is intact and hard, the back temperature of the substrate is below 300°C, and the thermal protection performance is excellent.

[0101] Figure 4 This is the state of the expansion layer of the coating obtained in Comparative Example 6 after 30 minutes of ablation. Figure 4It can be seen that when the coating system contains only one type of glass powder, more spherical ceramic structures appear in the expansion layer where the flame is directly burned. This is because during the burning process, molten droplets appear in the flame directly burned part of the coating. As the ablation test ends, the molten droplets cool to form ceramic balls. This shows that although the coating prepared in Comparative Example 6 can also undergo expansion and ceramicization reactions during the ablation process, the generation of molten droplets during its ceramicization process will also reduce the thermal insulation effect of the coating.

[0102] Embodiment 14

[0103] The method of Example 1 is followed, except that the glass powder consists of glass powder A, glass powder D, glass powder B and glass powder C in a weight ratio of 1:1:2:1.

[0104] The coating prepared in this example was not damaged during the ablation process, and the height of the expansion layer was 14.8 mm after 30 minutes of ablation, the expansion multiple reached 29.6 times, and the back surface temperature was finally stabilized at about 260°C.

[0105] By comparing Example 1 and Example 14, it can be seen that when the ceramic powder contains four glass powders with different melting points, the flame retardant and heat-insulating effects are similar to those when the ceramic powder contains three glass powders with different melting points.

[0106] Embodiments 15 to 18

[0107] The method of Example 1 is followed, except that: the content of the epoxy silicone resin in the film-forming material is adjusted, as shown in Table 4. In Table 4, the epoxy resin system is composed of epoxy resin and polyetheramine curing agent; the strength of the expansion layer after ablation for 30 minutes is characterized by placing a weight on the expansion layer until the expansion layer is damaged and recording the weight of the weight.

[0108] Table 4

[0109]

[0110] From Table 4 we can see that:

[0111] Example 1 and Examples 15 to 18 are fire retardant coatings prepared with different epoxy silicone resin contents. When the epoxy silicone resin accounts for 50% of the film-forming substance, the proportions of each component are the most coordinated, which not only ensures sufficient post-ablation expansion multiples, but also can form a sufficiently hard gradient ceramic structure, so the back temperature of the substrate is the lowest, only 260°C.

[0112] When the amount of epoxy silicone resin increases, the content of epoxy resin with carbon-forming ability decreases relatively. Although the ceramic strength of the expansion layer becomes higher, the expansion multiple of the coating will be greatly reduced after 30 minutes of ablation, which will lead to a sharp increase in the back temperature of the substrate and reduce the thermal protection ability of the coating to the substrate.

[0113] When the amount of epoxy silicone resin used is reduced, the content of substances promoting ceramicization in the film-forming material decreases relatively, and a hard and dense gradient ceramic expansion layer cannot be formed during continuous ablation. Although its expansion multiple increases, its density decreases, and the strength of the expansion layer also decreases, resulting in poor thermal protection performance for the substrate.

[0114] Figure 7 This is a graph showing the strength of the expansion layer after the coating was ablated for 30 minutes as obtained in Example 16. Figure 7 It can be seen that when two 500g weights are placed directly above the expansion layer, the total weight reaches 1kg, and a small area of ​​collapse occurs on the surface of the expansion layer, which indicates that the expansion layer after ablation in Example 16 can support a weight of about 1kg.

[0115] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A gradient ceramic intumescent fire retardant coating, characterized in that: The gradient ceramic intumescent fire retardant coating comprises the following components in weight percentage: Film-forming substances 20~50% Flame retardant 10~50% Ceramic powder 20~50% Reinforced fiber 0~10% Additives 0~10%; The ceramic powder comprises a first glass powder, a second glass powder and a third glass powder; The initial melting point of the first glass powder is 400-600° C.; The initial melting point of the second glass powder is 601-900°C; The initial melting point of the third glass powder is 901-1100° C.; The total weight percentage of the first glass powder, the second glass powder and the third glass powder in the gradient ceramic intumescent fire retardant coating is 15-45%; The film-forming substance is a mixture of epoxy silicone resin and at least one selected from epoxy resin, acrylic resin, phenolic resin, polyurethane resin, polyester resin, alkyd resin, and polystyrene resin; The weight percentage of the epoxy silicone resin in the film-forming substance is not less than 10%, based on the total weight of the film-forming substance; The flame retardant is a mixture of ammonium polyphosphate, melamine and at least one selected from aluminum hydroxide, magnesium hydroxide, pentaerythritol and dipentaerythritol; The gradient ceramic intumescent fire retardant coating comprises 10-20% ammonium polyphosphate and 5-10% melamine, based on the total weight of the gradient ceramic intumescent fire retardant coating; The ceramic powder further comprises at least one of silicon carbide, aluminum phosphate, calcium carbonate and zinc borate.

2. The gradient ceramic intumescent fire retardant coating according to claim 1, characterized in that: The weight ratio of the first glass powder, the second glass powder and the third glass powder is (1~6): (1~6): (1~6).

3. The gradient ceramic intumescent fire retardant coating according to claim 2, characterized in that: The weight ratio of the first glass powder, the second glass powder and the third glass powder is (1~3): (1~3): (1~3).

4. The gradient ceramic intumescent fire retardant coating according to claim 1, characterized in that: The reinforcing fiber is selected from at least one of silicon carbide fiber, aluminum oxide fiber, glass fiber, silicon oxide fiber, and carbon fiber; The reinforcing fiber has a diameter of 2-10 μm and a length of 0.05-3 mm.

5. The gradient ceramic intumescent fire retardant coating according to claim 1, characterized in that: The auxiliary agent is selected from at least one of a rheological agent, a dispersant, a thickener, an anti-settling agent, a leveling agent, a defoaming agent, and an anti-sagging agent.

6. Use of the gradient ceramic intumescent fire retardant coating according to any one of claims 1 to 5 in a power battery pack.

Citation Information

Patent Citations

  • Epoxy resin fireproof coating capable of ceramization

    CN107033734A

  • Environment-friendly organic silicon intumescent fireproof coating for transformer substation or converter station as well as preparation method and application of environment-friendly organic silicon intumescent fireproof coating

    CN119220174A

Cited By

  • An intumescent carbon layer reinforced water-based fireproof coating, a preparation method and application thereof

    CN120737696B